Filgrastim associations with CAR T‐cell therapy. Issue 5 (6th November 2020) - Gaut, Daria; Tang, Kevin; Sim, Myung Shin; Duong, Tuyen; Young, Patricia; Sasine, Joshua
Abstract: Little is known about the benefits and risks of myeloid growth factor administration after chimeric antigen receptor (CAR) T‐cell therapy for diffuse large B‐cell lymphoma (DLBCL). We present a retrospective analysis among 22 relapsed/refractory DLBCL patients who received CAR T‐cell therapy with axicabtagene ciloleucel. Filgrastim was administered by physician discretion to seven patients (31.8%), and the median duration of neutropenia after lymphodepleting therapy was significantly shorter for those patients who received filgrastim (5 vs 15 days, P = .016). Five patients (22.7%) developed infection in the 30 days post‐CAR T‐cell therapy with three patients being Grade 3 or higher. There was no difference in the incidence and severity of infection based on filgrastim use ( P = .274, P = .138). Among the seven patients that received filgrastim, six patients (85.7%) and four patients (57.1%) had evidence of cytokine release syndrome (CRS) and immune effector cell‐associated neurotoxicity syndrome (ICANS), respectively. Among the 15 patients that did not receive filgrastim, 8 patients (53.3%) and 7 patients (46.7%) had evidence of CRS and ICANS, respectively. There was no significant difference in the incidence of developing CRS or ICANS between the group of patients that received filgrastim and those that did not ( P = .193, P = .647). However, there was a significant increase in the severity of CRS for patients that received filgrastim compared to those that did not ( P = .042). Filgrastim administration after CAR T‐cell therapy may lead to an increase in severity of CRS without decreasing infection rates. Abstract : What's new Chimeric antigen receptor (CAR) T‐cell therapy in patients with relapsed/refractory diffuse large B‐cell lymphoma is limited by associated cytokine release syndrome, neurotoxicity, and cytopenias. Little is known about the benefits and risks of myeloid growth factor administration in CAR T‐cell therapy. This retrospective analysis reveals a significant increase in the severity but not the incidence of cytokine release syndrome in those patients that received filgrastim. There was no association of filgrastim use with the severity or incidence of neurotoxicity and infection rates. The findings call for caution in the use of myeloid growth factors in patients undergoing CAR T‐cell therapy.